2017
DOI: 10.1111/ijfs.13474
|View full text |Cite
|
Sign up to set email alerts
|

In vitro DNA damage protection and anti‐inflammatory effects of Tartary buckwheats (Fagopyrum tataricum L. Gaertn) fermented by filamentous fungi

Abstract: Summary The present work was designed to investigate the phenolic profiles, DNA damage protection and anti‐inflammatory effects of Tartary buckwheat fermented by Rhizopus oryzae 40469, Rhizopus oryzae 40503 and Rhizopus oligosporus 3152. Six phenolic compounds were characterised and quantified. Regardless of fermentation, rutin was the dominant phenolic substance in Tartary buckwheat. Fermentation significantly enhanced total phenolic and flavonoid contents, as well as DNA scission protection. Rhizopus oryzae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The total phenolic content (TPC) of each extract was measured according to a previously described Folin–Ciocalteu method with slight modifications (Huang et al ., ). The absorbance of the reaction solution was recorded with a microplate reader at 765 nm against a blank (SpectraMax M5, Molecular Device, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The total phenolic content (TPC) of each extract was measured according to a previously described Folin–Ciocalteu method with slight modifications (Huang et al ., ). The absorbance of the reaction solution was recorded with a microplate reader at 765 nm against a blank (SpectraMax M5, Molecular Device, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 97%
“…The total flavonoid content (TFC) was determined according to a previously reported colorimetric method (Huang et al ., ). The absorbance of the mixture was measured with a SpectraMax M5 microplate reader at 510 nm against a blank.…”
Section: Methodsmentioning
confidence: 97%
“…However, some studies showed that the extract with the highest amount of phenolics did not offer the strongest protective ability against DNA scission. Therefore, the total phenolic content, phenolic compositions, and chemical structures present in the phenolic extract may be in charge of DNA damage protection [ 25 ]. However, the potential mechanisms of DNA damage protection of phenolics need further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The overproduction of NO involves a series of events, including the reactions of free radicals and oxidants associated with several physiological disorders, such as acute and chronic inflammatory processes [ 5 , 25 ]. These processes eventually lead to tissue damage and organ dysfunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation